2005
DOI: 10.1007/s00423-005-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine—from best research evidence to a better surgical practice and health care

Abstract: As currently only 77 Cochrane reviews address surgical procedures; much work remains to be done to enlarge the number of high-quality and relevant reviews. Similarly, the number and quality of randomized controlled trials need to be increased in all surgical specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
0
19
0
13
Order By: Relevance
“…Evidence-based care is particularly challenging in surgery, for which there are few randomized trials to guide practice. 10,[24][25][26][27] We are not aware of any thorough studies examining the information needs of general surgeons, who, as do general practitioners, care for patients with a wide variety of conditions including cancer, a leading cause of premature death worldwide. One study reported that surgeons more frequently seek information from colleagues than family physicians do.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based care is particularly challenging in surgery, for which there are few randomized trials to guide practice. 10,[24][25][26][27] We are not aware of any thorough studies examining the information needs of general surgeons, who, as do general practitioners, care for patients with a wide variety of conditions including cancer, a leading cause of premature death worldwide. One study reported that surgeons more frequently seek information from colleagues than family physicians do.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews form a key role in the process of research synthesis, and therefore, make research findings available for the general medical community [39]. …”
Section: Knowledge Transfer Into Clinical Practicementioning
confidence: 99%
“…Nützlich ist in diesem Fall die genaue Kenntnis und Akzeptanz der Operationstechniken in den an der Studie teilnehmenden Prüfzentren [15]. Um eine möglichst hohe Übertragbarkeit (external validity) der Studienergebnisse zu erreichen, sollten insbesondere Studien zu Interventionen durchgeführt werden, die für die tägliche chirurgische Versorgung von Bedeutung sind [2]. Im Studienprotokoll ist es dann ausreichend, die Grenzen für einen solchen Versorgungskorridor festzulegen.…”
Section: Introductionunclassified